Childhood onset temporal lobe epilepsy: Beyond hippocampal sclerosis. (March 2016) - Mühlebner, Angelika; Breu, Markus; Kasprian, Gregor; Schmook, Maria T.; Stefanits, Harald; Scholl, Theresa; Samueli, Sharon; Gröppel, Gudrun; Dressler, Anastasia; Prayer, Daniela; Czech, Thomas; Hainfellner, Johannes A.; et al.
Abstract: Objective: Hippocampal Sclerosis (HS) is widely recognized as a significant underlying cause of drug-resistant temporal lobe epilepsy (TLE) in adults. In contrast, HS is a rare finding in pediatric surgical series, and a higher incidence of HS associated with cortical dysplasia (i.e. FCD type IIIa according to the new ILAE classification) than in adult series has been reported. Data about the electro-clinical characteristics of this subgroup are scarce. Methods: We studied 15 children and adolescents with drug-resistant TLE and HS who had anterior temporal lobe resection at our center with regard to electroclinical characteristics, MRI features and histopathology. Children in whom histopathology was consistent with Focal Cortical Dysplasia (FCD) type IIIa (n = 7) were compared with those who had HS only (n = 8). Results: Clinical characteristics associated with this highly selective subset of patients with FCD type IIIa were: the presence of febrile seizures during infancy, a shorter duration of active epilepsy and a lower age at epilepsy surgery. In addition, there were non-significant trends towards more extended abnormalities on both EEG and neuroimaging. We were, however, not able to find group differences with respect to neuropathologic subtyping of the HS. Conclusion: We present the first detailed description and comprehensive data analysis of children with FCD type IIIa. According to our results, this patient group seems to show a distinct clinical phenotype. Highlights: Homogeneous group of children with temporal lobe epilepsy. Novel insights into patients with FCD type IIIa. Features of a highly selective pediatric population with hippocampal sclerosis.